Qualitative analysis of patient motivation after suffering a stroke. Purpose of a clinical case (Cuestiones de Fisioterapia, 2004)
Motivation is an element that plays an essential role in the physical rehabilitation treatment. This term has to be understood as integrated by internal factors of the person, but also as influenced by external elements. Aspects such as patient's active level of participation in the whole process will have an effect on the patient's higher or lower motivation towards the procedure. After a stroke, many patients lack independence and need of the other's help. The role of patient's environment (professionals and family or the closest) is essential in this new scenario of their lives. About subject and methods, personal interviews to a person with a stroke, to his wife and two professionals, physiotherapist and physician, responsible of his physical rehabilitation program were carried out. About results, conflicts and disagreements emerged concerning the categorization of the patient as motivated or not. One of the main reasons was the different behavior that the patient showed in the treatment session and during the rest of the day. All the interviewees stated that they had a certain degree of responsibility motivating the patient, although this responsibility was jerarquized in different ways. The role of the family was vital though strenuous for the patient's wife. Then, a better level of communication between professionals and the inclusion of the patient as an active part of the process are key elements. Moreover, it is needed the development of programs to support the family. In conclusion, to take care of the «caregiver».